Daje naj
5 Rozwiąż równanie.
a) 2x - (x + 3) = 6+2x
b) 1/2(x+5)=2/3x +1


Odpowiedź :

Odpowiedź:

a)

2x - (x + 3) = 6+2x

2x - x - 3 = 6 + 2x

x - 3 = 6+2x / -2x + 3

-x = 9 /:(-1)

x=-9

b)

1/2(x + 5) = 2/3x + 1

1/2x + 5/2 = 2/3x + 1 /*6

3x + 15= 4x + 6 /-4x -15

-x = -9 /:(-1)

x=9

Odpowiedź:

a)

2x - (x + 3) = 6 + 2x

2x - x - 3 = 2x + 6

x - 2x = 6 + 3

-x = 9     /*(-1)

x = -9

b)

1/2(x + 5) = 2/3x + 1

1/2x + 5/2 = 2/3x + 1

1/2x - 2/3x = 1 - 2 1/2

3/6x - 4/6x = - 1 1/2

-1/6x = -3/2      /*(-6)

x = 3/2 * 6 = 9

Szczegółowe wyjaśnienie: